EFEKTIVITAS INTERVENSI REPEATED READING DENGAN STRATEGI SELF-MONITORING TERHADAP KELANCARAN MEMBACA SISWA KELAS 6 SD - Eka Rosita; Indriyana Rachmawati (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Reading fluency remains a challenge for some elementary school students and may hinder reading comprehension and overall academic achievement. Although repeated reading and self-monitoring have been widely investigated separately, studies integrating both strategies using a Single Subject Research (SSR) approach in elementary school settings remain limited. This study aimed to examine the effectiveness of repeated reading combined with a self-monitoring strategy in improving the reading fluency of sixth-grade elementary school students. The study employed a Single Subject Research approach using an A–B–A design involving two sixth-grade students at SDI Al-Irsyadiah Sangkulirang who experienced reading fluency difficulties. Data were collected through oral reading tests and structured observations using Correct Words Per Minute (CWPM) as the indicator of reading fluency. Data were analyzed descriptively using visual analysis within and across conditions. The results indicated that both participants demonstrated improved reading fluency following the intervention. Participant M improved from 27–34 CWPM during the baseline-1 phase to 33–51 CWPM during the intervention and maintained 44–51 CWPM during baseline-2. Participant RF improved from 77–84 CWPM to 77–118 CWPM during the intervention and maintained 111–120 CWPM during baseline-2. The Percentage of Non-overlapping Data (PND) was 100% for participant M and 75% for participant RF, indicating that the intervention was effective. These findings suggest that repeated reading combined with a self-monitoring strategy is effective in improving reading fluency among sixth-grade elementary school students. ABSTRAK Rendahnya kelancaran membaca masih menjadi kendala yang dialami sebagian siswa sekolah dasar dan dapat menghambat pemahaman bacaan serta keberhasilan belajar. Meskipun strategi repeated reading maupun self-monitoring telah banyak diteliti secara terpisah, kajian yang mengintegrasikan kedua strategi tersebut pada siswa sekolah dasar dengan pendekatan Single Subject Research (SSR) masih terbatas. Penelitian ini bertujuan menganalisis efektivitas intervensi repeated reading yang dipadukan dengan strategi self-monitoring terhadap kelancaran membaca siswa kelas VI SD. Penelitian menggunakan pendekatan Single Subject Research dengan desain A–B–A yang melibatkan dua siswa kelas VI SDI Al-Irsyadiah Sangkulirang yang mengalami hambatan kelancaran membaca. Data dikumpulkan melalui tes membaca nyaring dan observasi menggunakan indikator jumlah kata benar yang dibaca per menit (Correct Words Per Minute). Analisis data dilakukan secara deskriptif melalui analisis visual dalam kondisi dan antar kondisi. Hasil penelitian menunjukkan bahwa kedua subjek mengalami peningkatan kelancaran membaca setelah diberikan intervensi. Subjek M meningkat dari 27–34 kata benar per menit pada fase baseline-1 menjadi 33–51 kata benar per menit selama intervensi dan bertahan pada 44–51 kata benar per menit pada fase baseline-2. Subjek RF meningkat dari 77–84 kata benar per menit menjadi 77–118 kata benar per menit selama intervensi dan bertahan pada 111–120 kata benar per menit pada fase baseline-2. Nilai Percentage of Non-overlapping Data (PND) sebesar 100% pada subjek M dan 75% pada subjek RF menunjukkan bahwa intervensi tergolong efektif. Dengan demikian, repeated reading yang dipadukan dengan strategi self-monitoring efektif meningkatkan kelancaran membaca siswa kelas VI sekolah dasar.